POSITIONING OF HIGH SCHOOL / VOCATIONAL STUDENTS IN THE SELECTION OF UNIVERSITIES IN BANDAR LAMPUNG - Ida Damayanti Baringin Manik; Indriati Gultom (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study investigated the problem of student positioning in choosing a college. Focused on factors such as, economic factors with indicators of parental income and education costs, social factors with indicators of family environment and friendship environment, interest factors with indicators of desire to continue to college, and motivation to continue to college. This study investigated the problem of student positioning in choosing a college. Focused on factors such as, economic factors with indicators of parental income and education costs, social factors with indicators of family environment and friendship environment, interest factors with indicators of desire to continue to college, and motivation to continue to college. The purpose of this study was to determine the positioning of high school / vocational students in choosing universities. From the results of the study showed that the positioning of students in Bandar Lampung tends to have a strong desire to continue their education to university, the majority of students tend to choose to live in Bandar Lampung probably because they want to stay close to their families and home environment, and it was found that many students still have the desire to study at state university. This research uses a qualitative approach, which is a research method used to examine the natural condition of objects. In this study, the data collection technique used the distribution of questionnaires to several respondents of SMA/SMK in Bandar Lampung. By analyzing data using descriptive statistics, the presentation of data in this study is with narrative text. Furthermore, presenting data in addition to narrative text, also using diagrams and tables.